STUDY OF INNOVATIVE USE OF TECHNOLOGY IN EDUCATION - Pandey, Amit Kumar; Srivastav, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's modern era, the form of education is changing rapidly. Earlier, education was limited to books and blackboards, but now technology has made education more attractive, flexible and effective. The importance of technology is continuously increasing in today's education system. Innovative use of technology has made education more accessible, interesting, effective and personal, through which students are getting the latest knowledge, global resources and practical experience.